RAPID IDENTIFICATION OF HUMAN PATHOGENIC VIBRIO SPECIES USING MULTIPLEX PCR - A CASE STUDY - REENA KUMARI; AMIT RANJAN PRASAD; SHASHANK GUPTA; SHIPRA MOHAN TRIPATHI; SHWETA SINGH; PRASHANT VIKRAM SINGH; MADHULIKA SINGH; SHIVANI SINGH; TUSHAR JOSHI; SUBHENDRA; et al. (International Journal of Pharma and Bio Sciences, 2013)
There are several water-borne diseases which are highly pathogenic for humans. Amongst all, genus Vibrio plays a major role. In this case study of “RAPID IDENTIFICATION OF HUMAN PATHOGENIC VIBRIO SPECIES USING MULTIPLEX PCR” We have chosen salt water bodies such as sea and estuaries for sampling. To facilitate the identification of human-pathogenic species, we have used multiplex PCR to amplify gene regions in five species (V. cholerae, V. parahaemolyticus, V. vulnificus, V. mimicus and V. alginolyticus). The assay was tested on a sample of 82 Vibrio isolates for identification of five common human pathogenic vibrio species. Multiplex PCR was performed targeting the tox gene present in the five most common pathogenic vibrio species. After analysis of all the results we have found that salt water is having a higher concentration of vibrio species than freshwater & V.vulnificus was most abundant among all.